Assessment of the detoxification potential of rice husk sorbents (Experimental biology, 2021)
Heavy metals are a group of pollutants that have a negative impact on the body. Lead is widely used in the chemical industry in the production of paints, plastics, cosmetics, so the probability of ingestion of lead ions in the body is high. Lead compounds are highly toxic and are on a par with toxicants such as arsenic, mercury and Ben (a) pyrene. The mechanism of toxic action of lead is based on activation of free radical oxidation of cellular biomolecules and inactivation of antioxidant enzymes. Accordingly, to reduce the risk of intoxication, it is necessary to reduce the intensity of the formation of aggressive radicals involved in the oxidation chain reaction. To do this, today there are a number of tools that ultimately lead to a decrease in the concentration of lipoperoxidation products. One method is the chelation and sorption of xenobiotics, which are potentially dangerous in terms of induction of free radical processes.Our research was devoted to the assessment of the detoxification potential of rice husk sorbents in the context of their influence on the processes of peroxidation in the membranes of cells. The experiments were carried out in vivo. The animals received preparations from rice husks on the background of chronic intoxication with lead salts. As shown by the results of experiments, the inclusion in the diet of sorbents from rice husks can significantly reduce the toxic load on the body during prolonged poisoning with lead ions, as evidenced by the magnitude of oxidative stress. As a result of researches it is revealed that the crushed carbonized rice husk possesses high detoxification potential in comparison with the usual form, the level of peroxidation in hepatocytes and activity of antioxidant.
Keywords: ауыр металдар, күріш қауызы, асқын тотығу